ANALISIS IMPLEMENTASI PROGRAM KAMPUS MENGAJAR ANGKATAN 3 DALAM KEGIATAN MENGAJAR, ADAPTASI TEKNOLOGI DAN ADMINISTRASI PADA SEKOLAH DASAR NEGERI 1 MLANDANGAN - Triana Oktavia Oktavia Putri; Erna Puspita; Linawati Linawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Education is important for humans because a basic human need knowledge learned to be applied in the needs of life that will be faced. The number of teachers or educators who are few and lack competence has resulted in uneven learning in Indonesia, coupled with the emergence of the Covid-19 pandemic which caused learning to be disrupted and constrained by circumstances that made it impossible to meet and gather so that time and space for learning became limited. Kemdikbudristek created Kampus Mengajar Program as an effort to make learning in Indonesia better. Kampus Mengajar Program has partner schools, which are places where participants of Kampus Mengajar Program are placed. Selected partner school was the State Elementary School 1 Mlandangan. The purpose of this study was to determine the implementation of Kampus Mengajar Program on teaching activities, technology adaptation and administration at placement partner schools, State Elementary School 1 Mlandangan. The research method used is qualitative. There is an Implementation Stage in Kampus Mengajar program activities in the form of an initial stage, preparation stage, implementation stage and final result stage. The final result of this research is the implementation of teaching activities, technology adaptation and administration at SDN 1 Mlandangan.